Analisis Pengaruh Umur Dan CC Kendaraan Terhadap Emisi Gas Buang Pada Sepeda Motor Injeksi Mengunakan Bahan Bakar Ron 92 - Guspin Karnova; Een Tonadi; Antonius FA Silaen (LPPM Politeknik Jambi, 2025)
Abstract-This study aims to analyze the effect of vehicle age (year of assembly) and engine capacity (CC) on exhaust emissions of injection motorcycles using RON 92 fuel. The exhaust emissions tested include carbon monoxide (CO), hydrocarbons (HC), and carbon dioxide (CO₂). The method used is an experimental quantitative approach with direct texting on six EFI (Electronic Fuel Injection) technology motorcycles from various assembly years and engine capacities. Measurements were made using a gas analyzer under idle conditions for 30 minutes. The results showed that motorcycles with older assembly years (2009) and smaller engine capacities (110cc) tended to produce higher CO and HC emissions than newer vehicles. However, emission levels are also influenced by vehicle maintenance conditions, not just age and engine capacity. This study is expected to be a reference in efforts to control air pollution and increase public awareness of the importance of vehicle maintenance and the use of environmentally friendly fuels